Fine mapping of quantitative trait loci using advanced intercross lines of mice and positional cloning of the corresponding genes - Iraqi, F.A. (Informa UK Limited, 2000)
High-resolution mapping of quantitative trait loci (QTLs) is an essential step towards positional cloning and identification of the corresponding genes. Most QTL detection and mapping studies in mice have been carried out using F2 intercross and backcross populations. As a consequence of the limited number of recombination events in small chromosomal regions, this has generally permitted mapping to only relatively large confidence intervals of 20 to 40 cM. A number of po pulation designs have been proposed to increase recombination level in crosses. This includes advanced intercross lines (AIL) described by Daruasi and Soller (Genomics. 1995; 141: 1199-1207). In this report demonstration of the utility of the AIL approach for fine mapping of QTL, which previously had been mapped with 95 % confidence interval to 20 to 40 cM in a F2 intercross, will be presented. The methodological approaches to go from the fine-mapped QTL to the identification of the actual genes and mutations are discussed.